Implementasi Nilai-Nilai Hadis Sedekah dalam Program Makan Bergizi Gratis (MBG) di MTsN 1 Sleman - Aufa Fatchia Rahma; Nur Azizatul Haqiah; Winda Islamitha Nurhamidah; Marhumah (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
This study aims to analyze the implementation of hadith values regarding charity (ṣadaqah) within the Free Nutritious Meal Program (MBG) at MTsN 1 Sleman. This research employs a qualitative approach with a case study design involving one Islamic Education (PAI) teacher and seven students selected through purposive sampling. Data were collected through observation, indepth interviews, and documentation, and then analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that the MBG program received positive responses from both teachers and students, as it not only fulfills nutritional needs but also cultivates Islamic values such as charity, gratitude, cleanliness, responsibility, and moderation in food consumption. This study concludes that MBG has the potential to serve as a medium for internalizing Islamic values in education and contributes to strengthen.